Something old, something new [large type] - Clipston, Amy (Thorndike Press large print Christian romance series., 2023)
"In the decade since high school graduation, Christine Sawyer has realized her dream of opening Treasure Hunting Antique Mall. She's happy with her life-- if a bit lonely. She was always less lucky in love than her fraternal twin sister, Britney. Brent Nickelson is trying to come to grips with the shambles his life has become: after high school, an injury ended his planned football career, and now he's lost his construction business. When his great-aunt Midge asks for help putting her home on the market, the antiques in her house lead Brent to an unexpected partnership with Christine. Will they be able to realize the value of what's in front of them?"--